Evaluation of Post-operative Nursing Care of Psychological Support and Discharge Plan for Women Undergone Hysterectomy at Maternity Wards in Baghdad City’s Teaching Hospitals - Abd Al-Muhsen, Donia; Abdulwahid, Hala (Iraqi National Journal of Nursing Specialties, 2021)
Objective: The study aims at evaluating the psychological support and discharge plan from the hospital provided by nurses for woman undergone hysterectomy. Methodology: The study uses descriptive design and non-probability (convenient) sample which is consisted of (40) nurses from (8) teaching hospitals in the City of Baghdad within the maternity wards. The study is carried out from 11 November 2020 to 27 June 2021. A observational tool is developed to evaluate the psychological support and the discharge plan after surgery. Content validity and internal consistency reliability are determined through pilot study. Data are collected through the use of the questionnaire and data are analyzed through the use of descriptive and inferential statistical data analysis approaches. Results: Findings of the study show that all of the nurses have delivered inadequate postoperative nursing care. Recommendations: The study recommends that there is necessity of implementing training programs for nursing care after hysterectomy. And increase the number of nurses in this area to treat weakness in the wards. In addition, hospital management needs to play a strong role in monitoring patient care.